High-sensitivity troponin T levels before and after cardiac surgery and the 30-day mortality: a retrospective cohort study - Liang, Jian-Wei; Zhou, Min; Jin, Yong-Qiang; Li, Ting-Ting; Wen, Jiang-Ping (Frontiers in Cardiovascular Medicine, 2023)
Background: The suggested threshold level of cardiac troponin T elevation after cardiac surgery is not very clear, and the values recommended by various guidelines and literature reports are quite different. Methods: In this retrospective cohort study, we collected clinical data of patients who underwent heart surgery at Tsinghua University First Hospital between January 2015 and December 2022. Using the high-sensitivity cardiac troponin T levels (reference upper limit: 14 ng/L) measured at 1–3 days postoperation, the relationship between the cardiac troponin T level and the 30-day mortality risk was evaluated using Cox regression analysis. Results: Among the 3128 patients included in this study, the types of operations mainly consisted of coronary artery bypass graft (CABG, 1164, 37.2%), aortic valve replacement (AVR, 735, 23.5%), and other cardiac operations (1229, 39.3%). Within 30 days postoperation, 57 patients (1.8%) died and 72 patients (2.3%) developed major vascular complications. In patients undergoing CABG or AVR, the cardiac troponin T threshold level measured within one day postoperation related to an increased 30-day mortality was determined to be 3012 ng/L (95% CI: 1435–3578 ng/L), which is 218 times higher than the reference upper limit. In patients undergoing other cardiac operations, this threshold was 5876 ng/L (95% CI: 2458–8119 ng/L), which is 420 times higher than the reference upper limit. Conclusion: The high-sensitivity cardiac troponin T level associated with an increased 30-day mortality risk after cardiac surgery is significantly higher than the current recommendations for defining clinically important perioperative myocardial injury.